The Influence of Online Customer Reviews and Free Shipping Promotions on Purchase Decisions at PT Shopee Internasional Indonesia in Depok City, West Java - Amin Ilyas; Shalsha Allya Pratiwi; Erwin Rasyid (Jurnal Wacana Ekonomi, 2025)
This research seeks to examine the influence of online customer reviews and free shipping offers on purchasing decisions among Shopee users in Depok, West Java, both individually and jointly. A quantitative approach with a non-probability sampling technique was applied. The study population consisted of Shopee users in Depok who had made multiple purchases through the platform. Purposive sampling was employed to select respondents. Data were collected through primary sources in the form of questionnaires and analyzed using multiple linear regression. The findings indicate that both online customer reviews and free shipping promotions, whether considered separately or together, exert a positive and significant impact on purchasing decisions.